Clawback and Malus Provision: Is It Effective In Mitigating Risk-Taking Behavior? - Heni Desmaliana; Etik Kresnawati (Jurnal Reviu Akuntansi dan Keuangan, 2025)
Purpose: This study aims to examine the role of clawback and malus provisions in moderating the effect of executive compensation on bank risk-taking behavior. Methodology/approach: This study employed a quantitative approach with a population of all banking companies listed on the IDX for the period 2018-2023. The final sample included in the random effect regression model was 19 banks (114 fitm-year observations). All of the research data were obtained from the bank's annual report, available on their websites. Findings: This study uncovered that executive compensation exerted no effect on bank risk-taking behavior and was also not moderated by clawback and malus provisions. However, clawback and malus provisions have been proven to reduce bank risk-taking behavior as measured by Capital Adequacy Ratio. Practical implications: This study suggests that clawback and malus provisions are prominent factors in suppressing bank risk-taking behavior, which is represented by material risk takers (MRT). Therefore, law enforcement related to this provision needs to be strengthened to be more effective in controlling excessive risk-taking behavior in the banking sector. Originality/value: This study examines the effectiveness of POJK No. 45/POJK.03/2015 related to the obligation of banks to implement clawback and malus provisions in material risk taker’s compensation contracts.